THE INFLUENCE OF SERVICE QUALITY AND CUSTOMER TRUST TOWARD CUSTOMER LOYALTY: THE ROLE OF CUSTOMER SATISFACTION - Tigor Sitorus (International Journal for Quality Research, 2018)
This study aims at investigating and testing the mediated effect of Customer Satisfaction on the influence of the Service Quality and Customer Trust toward Customer Loyalty. This research was conducted in the five biggest national foreign exchange private banks that are listed in the Indonesia Stock Exchange up to the period of 2014, with the total sample of 170 customers, where after the monetary crisis in 2008, the business of bank in Indonesia was faced with the issue of customer trust that eventually influenced the customer loyalty. In this study, the Structural Equation Model by AMOS was used to analyze the data. The results show high Goodness of Fit and the simultaneous and individual tests also generated significant results. The results of data analysis show that: (1) Service Quality significantly gives positive influence to Customer Satisfaction, (2) Customer Trust has significant and positive influence on Customer Satisfaction, (3) Service Quality does not significantly give positive influence to Customer Loyalty, (4) Customer Trust significantly gives positive influence to Customer Loyalty, and (5) Customer Satisfaction significantly gives positive influence to Customer Loyalty. Therefore, the mediated effect of Customer Satisfaction on the influence of Service Quality and Customer Trust toward Customer Loyalty has more strength compared to the direct influence of Service Quality and Customer Trust toward Customer Loyalty.